Kidney Inflammation, Injury and Regeneration 2020 - Baer, Patrick C.; Koch, Benjamin; Geiger, Helmut (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Acute kidney injury (AKI) is still associated with high morbidity and mortality incidence rates, and also bears an elevated risk of chronic kidney disease in the sequel. Whereas the kidney has a remarkable capacity for regeneration after injury and may recover completely depending on the type of renal lesions, the options for clinical intervention are restricted to fluid management and extracorporeal kidney support. The development of novel therapies to prevent AKI, to improve renal regeneration capacity after AKI, and to preserve renal function-in both the short- and long-term-is urgently needed. This Special Issue includes papers investigating the pathological mechanisms of renal inflammation and AKI and diagnostics using new biomarkers. Furthermore, experimental in vitro and in vivo studies examining potential new approaches to attenuate kidney dysfunction are included, as well as review articles.